Enfermedades crónicas y capacidad funcional en adultos mayores del barrio Zamora Huayco de la ciudad de Loja - Sucunuta Sigcho, Cristina Alejandra (2023)
The general population has aged, resulting in older adults living with chronic diseases and both cognitive and motor deficits. These age-related functional limitations affect both mobility and independence and, as a consequence, quality of life. The objective of this research was to identify the existence of chronic diseases, to establish the degree of functional capacity by sex and age groups, and to establish their correlation in older adults in Zamora Huayco neighborhood in the city of Loja. A quantitative, crosssectional study was carried out with a sample of 83 older adults using the Katz Index test. Cardiovascular diseases were the most prevalent chronic diseases with 39.76% (n=33), with a predominance in men aged 65 to 74 and 75 to 84 years. When assessing functional capacity, 79.52% (n=66) showed no disability, with men predominating, while 14.46% (n=12) showed moderate disability, where men also stood out, and 6.02% (n=6) represented older adults with severe disability, predominantly women over 85 years of age. When the variables were related by means of the Chi Square calculation, a statistically significant relationship was found between Chronic Obstructive Pulmonary Disease and moderate disability with a p value of 0.020 and between Diabetes Mellitus and severe disability with a p value of 0.001. Concluding that functional capacity is affected by some chronic diseases presented in older adults